Evidence for an association between compound heterozygosity for germ line mutations in the hemochromatosis (HFE) gene and increased risk of colorectal cancer. - Robinson, J; Johnson, V; Rogers, P; Houlston, R; Maher, E; Bishop, D; Evans, D; Thomas, H; Tomlinson, I; Silver, A (2005)
Whereas a recent study reported an increased risk of colorectal cancer associated with any HFE germ line mutation (C282Y or H63D), other investigators have concluded there is no increased risk, or that any increase is dependent on polymorphisms in HFE-interacting genes such as the transferrin receptor (TFR). We have established the frequency of HFE mutations in colorectal cancer patients (n = 327) with a family history of the disease and randomly selected controls (n = 322); this design increases greatly the study's power. Genotyping for the TRF S142G polymorphism was also conducted on a large proportion of the study group. Using PCR, restriction enzyme mapping, sequencing followed by data analysis with Fisher's exact test and logistic regression, we show that the presence of any HFE mutation (Y282 or D63) was not associated with colorectal cancer risk (P = 0.57). In contrast, individuals compound heterozygous for both mutations (15 cases versus 5 controls) had thrice the odds of developing colorectal cancer (odds ratio, 3.03; 95% confidence interval, 1.06-8.61) compared with those with a single mutation. This finding did not quite reach statistical significance after allowing for multiple post hoc testing (P(observed) = 0.038 versus P = 0.025, with Bonferonni correction). Overall, our data indicate that individuals with a single HFE mutation, C282Y or H63D, are unlikely predisposed to develop colorectal cancer. However, risk of colorectal cancer might be increased by compound heterozygosity for the HFE mutations in the small number of subjects studied. TFR gene polymorphism was not an independent risk factor and did not modify the disease risk associated with HFE mutation.